PENGENDALIAN PERSEDIAAN PUPUK NPK MUTIARA PADA TOKO PERTANIAN PHONNA TANI DI PASAR PANORAMA KOTA BENGKULU - Joko Saputra; Saputra, Joko; Fariadi, Herri; Nurmalia, Ana (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
Fertilizer is nutrition or nutrients added to plants and currently, the use of fertilizer in agriculture is a necessity that cannot be ignored. One of the agricultural shops in Bengkulu City that provides fertilizer buying and selling services is the Phonna Tani shop at Panorama Market, NPK, Urea, KCl fertilizer, and many others are available. The purpose of this research is to determine inventory management, analyze inventory management, determine Safety Stock, and determine reorder points. The methods used in this research are qualitative and quantitative, with data results obtained from primary data and secondary data. Qualitative descriptive, EOQ (Economic Order Quantity) calculation techniques, Safety Stock calculation techniques, and Reorder Point calculation techniques are used in this research data analysis method. Based on the results of research, the management of inventory control of NPK Mutiara fertilizer at the Phonna Tani agricultural shop includes several stages, namely Planning, Organizing, Actuating, Controlling, and the FIFO method is used to manage fertilizer supplies. The results of calculations using the Economic Order Quantity (EOQ) method are 327 sacks per order with an ordering frequency of 3 times a year, so that in one year the number of fertilizer orders is 981 sacks, 9 sacks for safety stock and reorder points (Reorder point) 18 bags.